Neonatal subcutaneous fat necrosis as a close differential of neonatal sepsis: Case report and review of literature - Rahul Choudhary; Garima Sachdeva; Gaurav Katoch (Wolters Kluwer Medknow Publications, 2020)
Subcutaneous fat necrosis (SCFN) in a newborn is a rare self-limiting disorder associated with fatty tissue inflammation, mostly seen in term and postterm neonates. It is usually seen in the 1st week following a complicated delivery and is associated with lethargy, irritability, hypotonia, polyuria, polydipsia, vomiting, dehydration, and constipation. These neonates develop hypercalcemia, and C-reactive protein is persistently elevated. These features mimic neonatal sepsis. The characteristic lesions of SCFN are multiple erythematous nodules and these can guide to the final diagnosis. Here, we report a case of SCFN, which was initially misdiagnosed as neonatal sepsis and highlights the need for early diagnosis and treatment to prevent long-term complications. A literature search was done using PubMed, Medline, and Google Scholar databases using the mesh terms neonatal subcutaneous fat necrosis (SCFN) and subcutaneous fat necrosis (SFN).